Making the case for an international decade of radiocarbon - Eglinton, Timothy Ian; Graven, Heather D.; Raymond, Peter A.; Trumbore, Susan E.; Aluwihare, Lihini; Bard, Edouard; Basu, Sourish; Friedlingstein, Pierre; Hammer, Samuel; Lester, Joanna; Sanderman, Jonathan; Schuur, Edward A. G.; et al. (Philosophical transactions of the Royal Society. A, Mathematical, physical and engineering sciences, 2023)
Radiocarbon (14C) is a critical tool for understanding the global carbon cycle. During the Anthropocene, two new processes influenced 14C in atmospheric, land and ocean carbon reservoirs. First, 14C-free carbon derived from fossil fuel burning has diluted 14C, at rates that have accelerated with time. Second, ‘bomb’ 14C produced by atmospheric nuclear weapon tests in the mid-twentieth century provided a global isotope tracer that is used to constrain rates of air-sea gas exchange, carbon turnover, large-scale atmospheric and ocean transport, and other key C cycle processes. As we write, the 14C/12C ratio of atmospheric CO2 is dropping below pre-industrial levels, and the rate of decline in the future will depend on global fossil fuel use and net exchange of bomb 14C between the atmosphere, ocean and land. This milestone coincides with a rapid increase in 14C measurement capacity worldwide. Leveraging future 14C measurements to understand processes and test models requires coordinated international effort—a ‘decade of radiocarbon’ with multiple goals: (i) filling observational gaps using archives, (ii) building and sustaining observation networks to increase measurement density across carbon reservoirs, (iii) developing databases, synthesis and modelling tools and (iv) establishing metrics for identifying and verifying changes in carbon sources and sinks. - - This article is part of the Theo Murphy meeting issue 'Radiocarbon in the Anthropocene'.